If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*x+4/3 = (7/5)*x+37/15+2/5 // - (7/5)*x+37/15+2/5
(2/3)*x-((7/5)*x)+4/3-(37/15)-(2/5) = 0
(2/3)*x+(-7/5)*x+4/3-37/15-2/5 = 0
-11/15*x-23/15 = 0 // + 23/15
-11/15*x = 23/15 // : -11/15
x = 23/15/(-11/15)
x = -23/11
x = -23/11
| 0.3x+15.8=x-7.37 | | -0.5x+2.11=-0.3x+4.31 | | f(x)=x^2+5x | | 4m^2-3m=4 | | 1.2+0.1x=0.9 | | x-5/5-x-2/3=3X/10 | | 3.3x-51=2.3x+4 | | -0.04x=-3.6 | | 1/3x+1/2x=1/6 | | 2.7x+5-4.7x=9 | | x=3x+111 | | 9x+27=3x+135 | | 0.3x+0.4=-1.1 | | 34-2x=7x+23 | | 9x+72=3x+135 | | 3(k-2)-7=3k-(2k-3) | | 7x+6.46=5x+10 | | 1/5(3x-85)=4x | | x-4=2.68 | | 9x+72=3x+153 | | -36-8x=7x+22 | | -5y=4.45 | | 116-4x=14x+20 | | 3(k-2)-7=3(2k-3) | | x+1.6=9.2 | | 12x-(8x-2)=18 | | (2/14)=(t/63) | | 5m-13=-40+2m | | (r-s/r+s)(r^2-s^2/(r-s)(r+s)) | | 5m+4m+6+3m+m-6= | | (2/4)=(t/63) | | 2b^2-b=1 |